2014
DOI: 10.1016/j.jval.2014.08.563
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Validation of Kidney Disease and Quality of Life (Kdqol-Sftm 1.2) Instrument to Measure Health Related Quality of Life Of Indian Patients with Kidney Disease

Abstract: Objectives: Objective of the present study was to translate and validate the Kidney Disease Quality of Life-Short form 1.2 (KDQOL-SF TM 1.2) questionnaire in Hindi language for use in Indian Hindi speaking patients with kidney stone. MethOds: Forward and backward translations were performed. Intermediate version of Hindi questionnaire was developed and was used for pilot study (n= 20). Modified final version after pilot study was used for validation study. Results: Questionnaire was administered to patients (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…[41214162223] We found that lower hemoglobin levels were associated with poor KDCS and PCS whereas older age was associated with poor PCS. The presence of comorbidities had no impact on HRQoL.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…[41214162223] We found that lower hemoglobin levels were associated with poor KDCS and PCS whereas older age was associated with poor PCS. The presence of comorbidities had no impact on HRQoL.…”
Section: Discussionmentioning
confidence: 94%
“…[9] Validation studies have been undertaken in Indian languages including Kannada, Marathi, and Hindi. [101112] A study with a translated Tamil version has also been published. [13]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kidney Disease and Quality of Life-Short Form (KDQOL-SF) can be de ned as a kidney patient's usual or expected physical, emotional well-being, or social experience that consists a 36-item short form health survey (SF36) and kidney disease target areas (KDTAs). It is a comprehensive assessment of general health status and kidneydisease-related clinical characteristics [15].KDQOL-SF is an overall assessment of QOL in MHD patients.…”
Section: Measuring Toolsmentioning
confidence: 99%